PENGEMBANGAN MEDIA KARGUR TERHADAP REPRESENTASI SISWA PADA MATA PELAJARAN PPKN DI KELAS 2 MIN 7 KOTA MEDAN - Nurul Khoiriah Hairani; Abdul Gani Jamora (CV. ALIM'SPUBLISHING, 2024)
Development of Garuda Cardbo ard Learning Media for Student Representation in Civics Subjects in Class II MIN 7 Medan City. Learning media can be interpreted as a tool that carries messages and information between teachers and students. One of the learning media that can be applied for learning is Garuda cardboard media. Which is implemented in MIN 7 Medan City. This development research has the following problem formulation: (1). What is the validity of the Kargur learning media for the PPKn learning process for students in class 2 MIN 7, Medan City (2). What is the practicality of using Kargur media in the PPKn learning process for students in class 2 MIN 7 Medan City. (3). What is the effectiveness of kargur media on student representation after using kargur media on class 2 MIN 7 students in Medan City. The objectives of this research are: (1). How to validate the kargur learning media for the PPKn learning process for students in class 2 MIN 7 Medan City. (2). How to practically use kargur media in the PPKn learning process for class 2 MIN 7 students in Medan City. (3). What is the effectiveness of kargur media on student representation after using kargur media for class 2 MIN 7 students in Medan City. The results of this research are (1). ADDIE development model in the development of Garuda cardboard learning media: a. Analysis, which focuses on learning problems and student needs, b. Design, regarding product design in terms of Garuda cardboard learning media and preparation of rules use of media, c. development, this is based on the assessments, suggestions and comments of the validators according to their respective fields, d. implementation, in this research it was tested on 15 class II students at MIN 7 Medan City. e. Evaluation, aims to determine the success of research and development carried out on 15 students at MIN 7 Medan City. (2). The results of the feasibility of the Garuda cardboard learning media have a value of 4.5%, categorized as valid or usable but needing minor revisions from material experts, and 3.2% valid or usable but needing minor revisions.